RELEVANSI KONSEP AL-BAQA, AL-FANA, DAM ITTIHAD DALAM MENGHADAPI MODERNITAS - Siti Wafa Amani Mathar; Muhamad Ijlal Aziz; Maftu Ajmain (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study discusses the relevance of the concepts of Al-Baqā‘ (eternity), Al-Fanā’ (self-loss), and Ittiḥād (union) in the context of modernity. This qualitative study uses Sufism research methods with secondary data in the form of journals and books. Data analysis is carried out through inventory, classification, and interpretation. The results show that Al- Baqā‘ can be a strong ethical foundation in facing the challenges of globalisation such as consumerism and individualism. Al-Fanā’ is proposed as a strategy to overcome modern anomie, including rising crime rates and mental health problems. The concept of Ittihād is studied as a driver of unity in a multicultural society. Overall, Al-Baqa‘, Al-Fana’, and Ittihād are oflered as more holistic epistemological alternatives in dealing with the complexities of modernity.